Israel in the plan of God - Baron, David, 1855-1926 (Grand Rapids, MI Kregel, 1983)
Includes bibliographical references.
reprint. Originally published: The history of israel. London, Morgan and Scott, 1925.
Keywords: Bible -- History of Biblical events; Covenants (theology) -- Biblical teaching; Israel (Christian theology) -- Biblical teaching; People of God -- Biblical teaching; Typology (Theology).